041. A Case of Cholangiocarcinoma in A Young Adolescent - Djaja, Sebastian; Tobroni, Ahmad; Soenjoto, Dadik Agus; Suprapto, Bambang (JBN (Jurnal Bedah Nasional), 2024)
Background : Cholangiocarcinoma usually occurs in 50-70 years age group. Recent study showed an increased incidence in younger age group. We describe a case of Cholangiocarcinoma in an adolescent girl in order to understand its natural history. Case : A 16 year old girl presented with 2 months history of jaundice, itchyness, right upper quadrant abdominal pain, pale stool and dark urine. Initial investigation showed : Total Bilirubin 8.87, (Direct 3.53, Indirect 12.40), SGOT 75, SGPT 56, ALP 240, GGT 59, Hepatitis B and C negative, AFP 1.96, CA19-9 3.1, and CEA 5.1. Imaging showed dilated hepatic duct with 1.5cm mass in mid-Common Bile Duct (CBD). Due to unforeseen personal circumstances, surgery was done 16 months from onset of complaints. Tumor was found at junction of cystic duct + CBD. The CBD and Gallbladder was resected (with frozen section), lymph node dissected along hepatic artery, Roux-en-Y hepaticojejunostomy anastomosis and Jejuno-Jejunostomy anastomosis was performed. Histopathology showed Cholangiocarcinoma grade 2 with perineural + lymphovascular invasion, and malignant cells’ perineural invasion at proximal margin. She underwent adjuvant chemotherapy (Gemcitabine + Cisplatin). CT scan 6 months post Chemotherapy showed 3cm lesion in CBD. After a further 2 months of chemotherapy, CT evaluation showed no residual mass left. Conclusion: This highlight that despite significant time lapse from onset of symptoms, surgery with curative intent may still be considered. Secondly, chemotherapy is an extremely important part of the treatment, especially in presence of malignant cells at resection margin.